Overcoming researcher’s block symptoms:Creative strategies for research - Valarino, Elizabeth; Yaber O, Guillermo (Revista Interamericana de Psicología/Interamerican Journal of Psychology, 2017)
Among the symptoms of the All But Research (ABR) syndrome are researcher's block for thinking, creating or writing. These occur when writing up a research project, thesis, dissertation or faculty promotion report over long periods of time. In this article· we analyze researcher's block symptoms and describe specific intervention activities to them. We delineate the Research Project Management System which includes techniques to increase the flow of ideas and verbal fluency using creative processes. These techniques are combined with strategies for planning, systematic practice, time: and tasks management, continuous supervision and personal and group consultation. Its application with students and faculty showed an increase in research productivity both in terms of products and processes.